Effects of indirect sonication pretreatment and solvent extraction on the xanthone content and its antioxidant activities of freeze dried mangosteen (Garcinia mangostana Linn.) pericarp powder extracts - Aboutorab, Nasrin; Baharin, Badlishah Sham; Abdul Rahman, Russly; Selamat, Jinap; Chong, Gun Hean (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Garcinia Mangostana Linn. (mangosteen) belongs to the Guttiferae family; about 2/3 of the fruit weight is pericarp which is a great source of polyphenols compounds and xanthones with strong antioxidant and biological activity, but thrown out as a waste from the fruit processing industries due to its unpleasant astringency taste. Owing to the above concern, the extraction and utilization of these bioactive compounds for functional products is increasing. In present study effect of indirect sonication and solvent extraction of freeze dried mangosteen pericarp powder (MPP) on total xanthones, α- mangostin, total polyphenol content and its antioxidant activities were studied. Indirect sonication showed significantly higher total xanthone, α- mangostin content and α- mangostin percentage of MPP, irrespective of the sonication power and time (p < 0.05). Among the pretreated freeze dried MPP, low power 20 mins pretreatment showed higher α- mangostin content and a- mangostin percentage which was about 56.3 mg/g and 58.3%, respectively. Furthermore, indirect sonication pretreatment enhances the porosity of the MPP which can be clearly observed by the scanning electron microscope images with more loosen structure, whereas control showed more compact structure. This may enhance the release of total xanthones and α- mangostin during pretreatment. These results confirmed that indirect sonication with solvent extraction has synergistic effect on the release of total xanthones and a- mangosteen content of MPP.